A Theological Analysis Of Interfaith Dialogue And Its Relevance To Pluralistic Society Based On Hamka’s Tafsir Al-Azhar - Armiya, Armiya; Shalahudin, Henri; Choirunnissa, Ranya (Universitas Nurul Jadid, 2025)
Contemporary global challenges such as relativism, the fragmentation of meaning, and the increasing escalation of religion-related conflicts demonstrate the urgency of strengthening interfaith dialogue as a means of fostering social harmony, tolerance, and peace within society. In this context, this study analyzes Hamka’s interpretation of Qur’anic verses in Tafsir al-Azhar to explore how Islamic theological principles can guide constructive interreligious relations. Using a qualitative philosophical approach and thematic analysis of verses pertaining to interfaith relations, this research systematically identifies the key concepts emphasized by Hamka. The study finds that Hamka affirms three fundamental foundations of interreligious interaction: (a) the principle of universal human dignity, (b) justice and ethical responsibility toward others, and (c) guidance for peaceful coexistence rooted in Qur’anic moral values. The study also finds that Hamka underscores these principles as the basis for interreligious relations. Conceptually, this research contributes to the development of Islamic philosophy of religion; practically, it offers a normative framework to support tolerance, coexistence, and peace among diverse religious communities amid contemporary global challenges.